2011
DOI: 10.1111/j.1442-200x.2010.03212.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the pneumococcal conjugate vaccine on pneumococcal carriage in Turkish children

Abstract: Seven-valent conjugate vaccine induces long-term protection against carriage of VT S. pneumoniae in Turkish children. The ability of the conjugate vaccine to reduce transmission of antibiotic resistant S. pneumoniae may be possible if its introduction is coupled with a reduction in inappropriate use of antibiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
3
1
Order By: Relevance
“…In the Murad study, 63% of subjects were exposed to cigarette smoke, whereas in this study, 78-86.1% had been exposed. The prevalence of subjects who experienced pneumococcal colonization in this study was also higher than those found in studies in Finland (9%) and Turkey (9.7%) [22,23]. However, the prevalence was still lower than in subjects six weeks of age in Ethiopia in 2013 (32.7%) [24].…”
Section: Plos Onecontrasting
confidence: 64%
“…In the Murad study, 63% of subjects were exposed to cigarette smoke, whereas in this study, 78-86.1% had been exposed. The prevalence of subjects who experienced pneumococcal colonization in this study was also higher than those found in studies in Finland (9%) and Turkey (9.7%) [22,23]. However, the prevalence was still lower than in subjects six weeks of age in Ethiopia in 2013 (32.7%) [24].…”
Section: Plos Onecontrasting
confidence: 64%
“…Similarly, a study by Ercan et al. 93 from Turkey, reported on the resistance of S. pneumoniae to TMP-SMX at 63.3% followed by erythromycin at 40% and tetracycline at 33.3%. A study by Shibl et al.…”
Section: Prevalencementioning
confidence: 82%
“…The rate of intermediate resistance to penicillin reportedly ranged between 0% and 76.7%, and penicillin resistance ranged between 0% and 11.5%. The NP pneumococcal carriage rate among penicillin non-susceptible isolates (PNS, intermediate and resistant) reportedly ranged between 0% and 86.7% among healthy Turkish children before the introduction of the PCV [19][20][21][22][23]33,34]. In the present study, the PNS rate was 60%; Ozdemir et al [25] noted a 73% PNS rate (intermediate, 50.6%, and resistant, 22.4%) during the early post-PCV7 period.…”
Section: Discussionmentioning
confidence: 99%